Pengaruh Model Pembelajaran Discovery Learning Berbasis Proyek terhadap Kemampuan Berpikir Kreatif Siswa Kelas XII IPA SMA Negeri 8 Kota Jambi - Julianda, Nadia; Relawati, Relawati; Defitriani, Eni; Aisyah, Aisyah (Universitas Batanghari Jambi, 2022)
This research is backgrounded by the low ability to think creatively by students on the subject of discussion of compound opportunities. This is due to the less interesting learning process, the teacher only gives assignments and videos from the internet, while students only do the assignments without any discussion so learning mathematics very boring for students. To help students, a learning is needed that can optimize the ability to think mathematically creatively. One of the learnings that improve students' creative thinking skills is the discovery learning. The purpose of this study is to determine the influence of project-based discovery learning on the creative thinking ability of class XII of SMAN 8 Jambi City.This research is a quasi-experimental with Nonequivalent Pretest-Postest Control Group Design. The population used was all students of class XII IPA consisting of 236 students, the sample consisted of 65 students of the experimental class, namely XII IPA1 with the project-based Discovery Learning model and the control class, namely XII IPA2 with model being taught. The sample was selected by random sampling. The instrument used in this study was a test of creative thinking skills.Analysis using parametric statistical test Independent sample test test with SPSS for Windows Version 25.From the results of analysis is Asymp Sig. (2-tailed) is 0.000, it can be seen that Asymp Sig. (2-tailed) < 0.05 so that H0 rejected and H1 accepted. The final results, the project-based Discovery Learning learning model has a significant effect on students' creative thinking ability.